Prevalence of the 5‑HTT Linked Polymorphic Region among Faculty of Science Students and Its Association with General Mental Well‑Being - Asma Alilesh; Marwa Elwash; Ehsan Idris; Aboualkasem, Saad; Rowida Altomi; Fatima Alzahra’a Alshebani (AlQalam Journal of Medical and Applied Sciences, 2026)
The short allele of the 5-HTTLPR, located within the promoter of the serotonin transporter gene, has been linked with increased anxiety-related personality traits and affective disorders after exposure to stress. We aim to investigate the relationship between the short allele and the general well-being of Science Faculty students at the University of Misurata who have lived in Libya their whole lives and experienced the unrest of the past eight years. 226 participants were selected randomly, and the Oxford Happiness Questionnaire (OHQ) was used to assess their state of well-being. The OHQ results were used to divide the participants into three groups: the highest-scoring individuals, the lowest-scoring individuals, and those within the confidence interval for the mean of the sample. Members of each group were genotyped using conventional PCR analysis. Frequency test analysis showed the presence of a significant association between 5-HTTLPR and well-being in this sample, where the SS genotype was strongly associated with membership of the lowest-scoring group, while LL and LS were equally associated with that of the highest -scoring group.